Study of Incubation Duration After Degreening and Storage Methods on the Quality of Tangerine "Garut" (Citrus reticulata B.) - Tiara, Dede; Poerwanto, Roedhy; Efendi, Darda (Journal of Tropical Crop Science, 2019)
Ripened citrus fruits with an orange rind have a higher market demand relative to unripen citrus with a green rind. This research was aimed to evaluate the combination of post-degreening incubation duration before storage with the type of storage to increase orange rind color and storage life of citrus fruit. A randomized block design with two factors was used; the first factor was post-degreening incubation duration before storage that comprised of without incubation, incubation for two and four days. The second factor was storage method that comprised of storage at room temperature (29 ± 1oC), at 18 ± 1oC, waxing and storage at room temperature, waxing and storage at 18 ± 1oC. The result shows that post-degreening incubation duration that increased orange color of citrus rind was four days. The citrus which was stored at 18 ± 1oC had the smallest fruit weight loss. The best treatment combination which increased orange color formation and had lower percentage of fruit weight loss was a combination of 4 days incubation after degreening and storage at 18± 1oC.